Bordir Kerancang di Kota Bukittinggi (Studi Kasus di Usaha Sulaman Ambun Suri) - Hervilas, Vivi; Adriani, Adriani; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The oldest and famous embroidery business in Bukittinggi is Sulaman Ambun Suri. This study aimed to describe embroidery motifs, forms and techniques of making embroidery kerancang in Ambun Suri. The method used is a qualitative descriptive. The type of data in the form of primary data and secondary data. Informant are the leaders and craftsmen in Ambun Suri. The technique of collecting data through observation, interviews and documentation. Data analysis techniques are data reduction, data presentation, and conclusions. Extension of the validity of the data with observations, increased observation and triangulation. The study states that the embroidery motifs in Ambun Suri are very diverse which are inspired by nature. Embroidery has a decorative motif with naturalistic shapes, geometric shapes, and decorative shapes made up of the main motif, complementary motifs, and patterns filler. There are 23 shapes of kerancang used. The making of the embroidery is done by using a manual sewing machine by sewing it directly using embroidery thread branded „double penguin‟. The stage of making embroidered kerancang is starting from tracing the motif, mengkuku thatch or mensuji motif, cutting, embroidering and the last thing is finishing process by smoothing embroidery.Keywords: Bordir Kerancang, Motif Bordir, Bentuk Kerancang, Teknik Pembuatan Bordir1Prodi Pendidikan